Lenalidomide‐based maintenance therapy reduces TNF receptor 2 on CD4 T cells and enhances immune effector function in acute myeloid leukemia patients. Issue 8 (16th May 2014) - Govindaraj, Chindu; Madondo, Mutsa; Kong, Ying Ying; Tan, Peter; Wei, Andrew; Plebanski, Magdalena
<x xml:space="preserve">Abstract</x> A major limitation to improved outcomes in acute myelogenous leukemia (AML) is relapse resulting from leukemic cells that persist at clinical remission. Regulatory T cells (Tregs), which are increased in AML patients, can contribute to immune evasion by residual leukemic cells. Tumor necrosis factor (TNF), a pro‐inflammatory cytokine present at high levels within patients, can induce TNF receptor‐2 (TNFR2) expression on Tregs. We hypothesized that since TNFR2 is required for Treg stabilization and TNFR2+ Tregs are potent suppressors, targeting TNFR2+ Tregs may restore the effectiveness of immune‐surveillance mechanisms. In this pilot study, we report AML patients in clinical remission have substantially increased levels of TNFR2+ T cells, including TNFR2+ Tregs and impaired effector CD4 T cell function with reduced IL‐2 and IFNγ production. The immunomodulatory drug, lenalidomide, and the demethylating agent, azacitidine have been moderately successful in treating AML patients, but their combined effects on TNFR2+ T cells, including Tregs are currently unknown. Our data indicates that although treatment with lenalidomide and azacitidine increased cytokine production by effector T cells in all patients, durable clinical remissions may be observed in patients with a concomitant reduction in TNFR2+ T cells and TNFR2+ Tregs. In vitro studies further demonstrated that lenalidomide can reduce TNFR2 expression and can augment effector cytokine production by T cells, which can be further enhanced by azacitidine. These results indicate that reduction of TNFR2+ T cells in AML postremission phase may result from combined azacitidine/lenalidomide therapy and may contribute to an improved clinical outcome. Am. J. Hematol. 89:795–802, 2014. © 2014 Wiley Periodicals, Inc.